The Impact of Heart Rate Response During 48-Hour Rewarming Phase of Therapeutic Hypothermia on Neurologic Outcomes in Out-of-Hospital Cardiac Arrest Patients. Issue 9 (September 2018) - Inoue, Akihiko; Hifumi, Toru; Yonemoto, Naohiro; Kuroda, Yasuhiro; Kawakita, Kenya; Sawano, Hirotaka; Tahara, Yoshio; Hase, Mamoru; Nishioka, Kenji; Shirai, Shinichi; Hazui, Hiroshi; Arimoto, Hideki; et al.
Abstract : Objectives: Bradycardia during therapeutic hypothermia has been reported to be a predictor of favorable neurologic outcomes in out-of-hospital cardiac arrests. However, bradycardia occurrence rate may be influenced by the target body temperature. During therapeutic hypothermia, as part of the normal physiologic response, heart rate decreases in the cooling phase and increases during the rewarming phase. We hypothesized that increased heart rate during the rewarming phase is another predictor of favorable neurologic outcomes. To address this hypothesis, the study aimed to examine the association between heart rate response during the rewarming phase and neurologic outcomes in patients having return of spontaneous circulation after out-of-hospital cardiac arrest. Design: A secondary analysis of the Japanese Population-based Utstein style study with defibrillation and basic/advanced Life Support Education and implementation-Hypothermia registry, which was a multicenter prospective cohort study. Setting: Fourteen hospitals throughout Japan. Patients: Patients suffering from out-of-hospital cardiac arrest who received therapeutic hypothermia after the return of spontaneous circulation from 2005 to 2011. Intervention: None. Measurements and Main Results: This study enrolled 452 out-of-hospital cardiac arrest patients, of which 354 were analyzed, and 80.2% survived to hospital discharge, of which 57.3% had a good neurologic outcome. Heart rate response was calculated using heart rate data recorded during therapeutic hypothermia in the abovementioned registry. Heart rate response in the rewarming phase (heart rate response-rewarming) was calculated as follows: (heart rate [post rewarming]–heart rate [pre rewarming])/heart rate (pre rewarming) × 100. The primary outcome was an unfavorable neurologic outcome at hospital discharge, that is, a Cerebral Performance Category of 3–5. Multivariable logistic regression analysis was performed to determine the association between heart rate response-rewarming and unfavorable neurologic outcomes. Multivariable logistic regression analysis showed that heart rate response-rewarming was independently associated with unfavorable outcomes (odds ratio [per 10% change], 0.86; 95% CI, 0.78–0.96; p = 0.004). Conclusions: Increased heart rate in the approximately 48-hour rewarming phase during therapeutic hypothermia was significantly associated with and was an independent predictor of favorable neurologic outcomes during out-of-hospital cardiac arrest. Abstract : Supplemental Digital Content is available in the text.